Analisis Resepsi Khalayak Terhadap Makna Muallaf Pada Iklan Online Bukalapak “A Stranger – A Ramadan Story” - Delya, Alfira Nanda; Sakuri, Anggy Aglevia; Sugiharto, Clarissa Erine (CommLine, 2022)
As digital technologies dramatically reshape industry after industry, the selection of media for advertising is increasingly diverse. Online media is one of the mainstream media which is currently used as a tool for advertising with the aim of promoting a product widely and easily accessible to anyone with an internet connection. One of the companies that often advertise through online media is Bukalapak, which is one of the largest online marketplaces in Indonesia. This study aims to identify the audience's interpretation of the meaning of "Muallaf". The theory used is reception analysis, with a type of qualitative research that focuses on the meaning and message of "Muallaf" in the advertising. The data were obtained through in-depth interviews with informants who were not taken randomly but through purposive sampling, in order to get wise informants in responding to advertisements that the researchers used as case studies. The object of research is the Bukalapak Online Youtube advertisement "A Stranger - A Ramadan Story". The results of the study found that there were informants who showed a dominant position (hegemonic reading) that, the meaning of Muallaf was well described and while the other informants indicated a negotiated position (negotiated reading) or basically accepted but felt the image of a convert to Islam in Bukalapak's "A Stranger - A Ramadhan Story advertisement." is incorrect